GROWTH AND MBMS STUDIES OF REACTION-MECHANISMS FOR INXGA1-XAS CBE - Singh, N; Foord, J; Skevington, P; Davies, G (1992)
The reaction mechanism involved in the growth of InxGa1-xAs lattice matched to InP by chemical beam epitaxy (CBE) was investigated using growth and modulated beam mass spectrometry studies. Emphasis was placed on elucidating how variations in substrate temperature, indium composition and arsenic overpressure influence growth kinetics and how sensitive changes in experimental conditions bring about deviations in the ideal stoichiometry (In0.53Ga0.47As) required for lattice matching to InP. Our observations indicate that the compositional variations in the InGaAs stoichiometry at high temperatures (> 485°C) arise because of the changes in the DEG decomposition: desorption branching ratio which is controlled by a temperature- and arsenic pressure-dependent surface population of indium atoms. The low temperature behaviour is governed by the availability of metal surface sites for triethylgallium decomposition which is increased by the presence of surface indium atoms. © 1992.